Les aspects culturels dans le film français intitulé le Sixième Enfant - Rohmawatiningrum, Silam; Eko Agustiningrum, Tri (Universitas Negeri Semarang, 2025)
This research aims to determine the cultural aspect of the Le Sixième Enfant film based on CECRL criteria. The data of this research are snippets of scenes (picture/nonverbally), words, clauses, or sentences (verbally) in the le Sixième Enfant film that have cultural elements that fit with the criteria of Common European Framework of Reference for Languages (CECRL). Data was collected using observation methods and followed by the documentation method. The researcher uses the data reduction method, presents data, and draws conclusions. It means that the researcher is using her abilities to analyze the data. From 69 data that have been studied, all elements (seven elements) of culture were found according to (Conseil de l’Europe, 2000). The seven elements are daily life, found in 12 snippets; social standard of life, found in 5 snippets; interpersonal relationship, found in 13 snippets; values, beliefs, and behavior, found in 10 snippets; body language, found in 11 snippets, life manner found 11 snippets, and ritual behavior found seven snippets.